Determinants of Labor Force Participation and Wages in Thailand: What is the Role of the Informal Sector?*. Issue 3 (27th November 2020) - Thaiprasert, Nalitra; Leurcharusmee, Supanika; Jatukannyaprateep, Peerapat; Sirisrisakulchai, Jirakom
Abstract : There has been a perennial debate on why the informal economy exists and grows in developing countries around the world. The present study focuses on the case of Thailand, one of the countries with the highest share of informal activities, to clarify whether its informal workers participate in the informal sector voluntarily or involuntarily. The confirmation matters for the design of government policies and public welfare. We separated the study into two levels. First, at the national level, we used the finite mixture model to examine the 2010 Population and Housing Census and estimate the wage equations for formal, voluntary informal and involuntary informal workers. Second, we focused on a local area for the case of Chiang Mai city, where we surveyed a sample of 393 informal business owners to understand their decision to participate in the informal sector. From both levels of study, we found heterogeneity among the informal workers, who could be classified into voluntary and involuntary groups. While those in the voluntary group stay in the informal sector because workers prefer time flexibility, those in the involuntary group stay because of family burdens. Both levels of data also showed that the Thai informal sector is dominated by the voluntary group (>70 percent).